Review of Maqashid Sharia Related to Shopee PayLater Affects Flexing Lifestyle - Lanina Puspita Lotusia Permata Agzah; Achmad Fageh (al-Afkar, Journal For Islamic Studies, 2024)
Shopee PayLater is a payment method in the form of an instant loan that can provide convenience by receiving goods first but payment can follow in the next month or in installments. Spay Later is able to make payment processes faster, easier, more efficient and safer. This makes it easier for Flexing actors to buy whatever items they want for the sake of a lifestyle on social media without thinking about the origin of the items they buy. Is it halal or haram. This research method is a literature review or literature review. The type of research used is library research, namely reviewing articles. The purpose of this writing is to provide new literature and findings regarding today's hedonism and also technological advances which can influence someone to neglect their own welfare, some of them cannot differentiate between needs and desires. The results of this research are related to Shopee PayLater influencing a person's Flexing lifestyle viewed through the lens of Al-Maqashid Asy-Syariah where there are findings that apart from being contrary to the Al-Quran and Al-Hadith, the Flexing lifestyle is also influenced by the convenience of the new Shopee PayLater feature. in accordance with the principles of Al-Kulliyat Al-Khomsah needs.